Kerugian Keuangan Negara Dalam Pengadaan Alat Kesehatan Di Indonesia - Ahmad Feri Tanjung; Rizkan Zulyadi; Ronald Hasudungan Sianturi (Fakultas Hukum Universitas Islam Indonesia, 2019)
he financial loss of the state is determined by many factors leading the method of calculating the state financial loss to be unstandard and then causing uncertainty in calculation of the state financial loss, including in the procurement of medical devices. This study aims to (a) analyze the factors determining the financial loss of state in the procurement of medical devices and (b) to analyze the method used to calculate the financial loss of the state in the procurement of medical devices. This is a normative juridical research using a conceptual approach and a regulatory approach. The data used were secondary data collected through literature. From the research results, first, it can be concluded that the factors determining the fiancial loss of state in the procurement of medical devices were the factors of goods effectiveness as needed. The procurement of medical devices that has the nature of the goods is a unit to be utilized as needed, and then the method of calculating the financial loss of state used is the method of calculating the total loss, but if the medical devices that have properties can be utilized separately, the calculation of financial losses used is net loss. Another factor affecting was the price reasonableness if the procurement of medical devices can be utilized as needed but the price of medical devices exceeds the reasonableness. Second, the method of calculating financial loss of stated used due to the price reasonableness was the price reasonableness method.